ADVERSE EFFECTS OF NON STEROIDAL ANTI INFLAMMATORY DRUGS ON GERIATRIC PATIENTS. A SCIENTIFIC REVIEW - Ali Fayez Abdu Alzubaidi, Saad Mukhlef Almutairi, Sultan Saud Alahmadi, Hani Abdallah Habhab, Ahmad Mohammad Alghamdi, Nada Muteb Almutairi, Shaher Mohammed Aljedaani, Ibrahim Ali Ahmed Abadi, Jaber Ali Ahmed Abadi,; Osama Talha Hawsawi, Ibrahim Mohammed Abdullah Alabdullah (Chelonian Research Foundation, 2022)
Non steroidal anti inflammatory drugs (NSAIDs) are one of the most commonly prescribed pain medications. NSAIDs are potent therapeutics for relieving pain and reducing inflammation. However, they are associated with several adverse effects, such as gastrointestinal bleeding, cardiovascular complications, and NSAID-induced kidney damage. Given the aging of our society, it is imperative to possess a thorough understanding of this category of drugs in the elderly. Consequently, we examined the effects of drugs in the body, the current recommendations for the use of NSAIDs, the negative effects that NSAIDs can have, and how NSAIDs can interact with other regularly used medications in older adults. Key words: NSAIDs, non-steroidal anti-inflammatory drugs, elderly, geriatric.